Pausing the Fight Against Malaria to Combat the COVID-19 Pandemic in Africa: Is the Future of Malaria Bleak? - Nghochuzie, Nora Nganyewo; Olwal, Charles Ochieng'; Udoakang, Aniefiok John; Amenga-Etego, Lucas Naam-Kayagre; Amambua-Ngwa, Alfred (Frontiers in Microbiology, 2020)
Malaria remains a major global health burden killing hundreds of thousands annually, especially in sub-Saharan Africa. In 2019, a Phase IV Expanded Programme on Immunizations (EPI) linked malaria vaccine implementation was underway, but in late December 2019, a novel pneumonia condition (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), with many clinical, epidemiological and biological parallels to malaria was reported in Wuhan, China. COVID-19 is spreading rapidly and as of 13th May 2020, more than 292,807 persons had died from COVID-19. Children under 5 years who suffer high malaria attributable mortalities are largely asymptomatic for COVID-19. Considering that malaria burden is highest in low-income tropical countries with little capacity to fund malaria control and eradication programs, the fight against malaria in these regions is likely to be hampered owing to suspension of seasonal malaria chemotherapy due to lockdown, distribution of insecticide-treated bed nets and limited access to healthcare. COVID-19 has disproportionately affected the developed countries, threatening their donation capacity. This is likely to thwart malaria control efforts in the low-income regions. Here, we present perspectives on the collateral impact of COVID-19 on malaria, especially in Africa.